The Educational Game “Indonesian Tribes” for the Kindergarten Students - Pikir Wisnu Wijayanto; Yahdi Siradj (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2017)
This study describes the educational game “The Indonesian Tribes” as a multimedia application to facilitate the learning activities for the students in kindergarten. This multimedia application is designed to help the students to recognize the several tribes and cultures in Indonesia such as the traditional clothes, houses, dances, and the gamelan musical instruments. This application is equipped with a Kinect sensor technology to detect the external trigger such as speech and gesture (motion) recognition that will encourage the students’ enthusiasm in playing and learning activities. It is in line with their characteristics who love to play and learn with their own imagination. This game education is also completed with audio-visual animations in various contents and interactive nature with a simple English description and instructions.Except where otherwise noted, content on this site is licensed under a Creative Commons Attribution 4.0 International License